Effect of platelet‐rich plasma on reconstruction with nerve autografts. Issue 2 (29th December 2016) - Teymur, Hakan; Tiftikcioglu, Yigit Ozer; Cavusoglu, Turker; Tiftikcioglu, Bedile Irem; Erbas, Oytun; Yigitturk, Gurkan; Uyanikgil, Yigit
Abstract: Despite advances in understanding of peripheral nerve injuries and regeneration and advances in surgical techniques, successful outcomes cannot be guaranteed after reconstructive surgery. Platelet‐rich plasma (PRP) has been reported to have positive effects on nerve regeneration, as well as on tissue healing. The present study was designed to evaluate the effect of PRP on nerve‐grafted defects. Sprague–Dawley rats were divided into four surgery groups ( n = 7 in each). A 1‐cm long nerve defect was created in the upper thigh and then reconstructed using a nerve autograft in all groups. The wet muscle weights, electromyographic findings, and histomorphologic changes were evaluated 10 weeks later. As shown by both the electromyographic ( p < 0.001) and histomorphologic findings ( p < 0.001), PRP had more positive effects on nerve gap reconstruction in Group 3 then Group 4 as compared to the control groups. The present study is novel in that it evaluated the regeneration effect of PRP on a large nerve defect reconstructed with a nerve graft rather than primary repair. The results are encouraging for further experimental studies on the role of PRP in nerve healing.